РИЗИКИВИНИКНЕННЯДЕФОЛТУТАШЛЯХИЙОГОЗАПОБІГАННЯВКОНТЕКСТІПІДТРИМКИФІНАНСОВОЇБЕЗПЕКИУКРАЇНИ - Prokopets, Liudmyla; Ostafychuk, Petro (My University, 2023)
МетоюданоїстаттієвисвітленняризиківвиникненнядефолтууконтекстіфінансовоїбезпекиУкраїни. Здійсненоаналіззаходівдержавистосовнозабезпеченняфінансовоїбезпекикраїни. Узагальненопідходидо дефініцій «дефолт» та «фінансовабезпекадержави». ПроаналізованотаданохарактеристикуключовихризиківдефолтутазагрозфінансовійбезпеціУкраїни. Здійсненоаналізнауковихбаченьщодоїхкласифікації. НаданорекомендаціїстосовнореалізаціїдійщодозменшенняризиківусферіфінансовоїбезпекиУкраїни, завдякидержавнійполітицітаправовихмеханізмівїїзабезпечення. Виокремленозаходи, якіповинназдійснюватидержававсферіфінансовоїбезпекиУкраїни. Висвітленонеобхідністьудосконаленнянадержавномурівніаналізутамоніторингуризиківякіспричинюютьдефолт; здійснення дієвих заходів, зорієнтованихназменшеннянегативнихнаслідківтаїхподолання. Розкрито, щоякісневтіленняорганізаційноготазаконодавчогомеханізмівзабезпеченняфінансовоїбезпекидастьможливістьдобитисядлядержавитакихрезультатівякпокращеннярівнядовіридодержавнихорганів, створити соціальну стабільність, зменшитивпливсвітовихфінансовихкризнаекономікукраїни.
RISKS OF DEFAULT AND WAYS TO PREVENT IT IN THE CONTEXT OF SUPPORTING THE FINANCIAL SECURITY OF UKRAINE
The purpose of this article is to highlight the risks of default in the context of the financial security of Ukraine. An analysis of state measures to ensure the financial security of the country was carried out. The approaches to the definitions of «default» and «financial security of the state» are summarized. The key risks of default and threats to the financial security of Ukraine were analyzed and described. An analysis of scientific visions regarding their classification was carried out. Recommendations are given regarding the implementation of actions to reduce risks in the financial security of Ukraine, thanks to the state policy and legal mechanisms for ensuring it. The measures that the state should implement in the field of financial security of Ukraine are highlighted. The need to improve the analysis and monitoring of risks that cause default at the state level is highlighted; implementation of effective measures aimed at reducing negative consequences and overcoming them. It was revealed that the high-quality implementation of organizational and legislative mechanisms for ensuring financial security will make it possible for the state to achieve such results as improving the level of trust in state bodies, creating social stability, and reducing the impact of global financial crises on the country’s economy. The proposed tasks will make it possible to improve trust in public authorities, predict financial crimes, reduce the shadow economy and administrative violations, ensure financial conditions for social stability, reduce the impact of global financial crises and prevent default; to attract foreign investments for the development of the national economy. Risks that cause default are a negative phenomenon for the country. As a result of the study, it was determined that the negative consequences affect financial security - the budget, debt, banking, monetary credit, currency, security of the non-banking financial sector. The main goal of default prevention is the state systematization of methods and means of risk manifestation and counteracting their consequences on the state economy and financial security in particular. A number of problems can be bypassed with the help of legislative and state regulation of issues of ensuring financial security of Ukraine.
Keywords: ризики; дефолт; фінансова безпека держави; фінансова стабільність; ризики у сфері фінансової безпеки; risks; default; financial security of the state